Acute Bacterial Prostatitis – a review of current literature - Piotr Zając; Jan Węgrzyn; Łukasz Fijałkowski; Aleksandra Nosal; Adam Czarnecki; Aleksandra Galanty-Ochyra; Karolina Serwońska; Artur Pastuszka; Olga Jabłońska; Filip Klimas (Journal of Education, Health and Sport)
Introduction and purpose